MALDI-MS analysis of disaccharide isomers using graphene oxide as MALDI matrix. (16th April 2021) - Lee, Dabin; Kim, Yeoseon; Jalaludin, Iqbal; Nguyen, Huu-Quang; Kim, Minsun; Seo, Jungju; Jang, Kyoung-Soon; Kim, Jeongkwon
Highlights: Graphene oxide was used as a MALDI matrix for disaccharide isomer analysis. Unique cleavage pattern was observed for each disaccharide isomer in MALDI-MS. Potential for quantitative disaccharide isomer analysis was demonstrated using honey samples. Abstract: Disaccharides are sugars composed of two monosaccharides joined by a glycosidic linkage. The specific properties of a disaccharide depend on the type of the glycosidic linkage and the identity of the two component monosaccharides. In this work, seven disaccharide isomers (gentiobiose, isomaltose, melibiose, lactose, maltose, cellobiose, and sucrose) were analyzed by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) using a graphene oxide matrix. Each disaccharide was identified by its unique cleavage pattern. To determine the feasibility of quantitative analyses based on specific fragment patterns, mixtures of sucrose with cellobiose or maltose were prepared at different ratios and analyzed by MALDI-MS, where a strong linear correlation was observed between the relative peak intensity of the sucrose fragment peak at m / z 185 and the amount of sucrose in the mixture. The calibration curve was successfully applied to obtain the relative amount of maltose and sucrose in four different honey samples.